Building a Taxonomy to Understand Health Care Worker's Response to Workplace 'Pressure' in Complex, Volatile and Emergency Situations. (13th September 2021) - Zavala-Calahorrano, Alicia M.; Plummer, David; Day, Gary
This research aims to better understand performance under pressure as experienced by health and emergency staff in the workplace. Three basic questions underpin the work: (1) how do health and emergency workers experience and make sense of the 'pressures' entailed in their jobs? (2) What impacts do these pressures have on their working lives and work performance, both positively and negatively? (3) Can we develop a useful explanatory model for 'working under pressure' in complex, volatile and emergency situations? The present article addresses the first question regarding the nature of pressure; a subsequent article will address the question of its impact on performance. Using detailed interviews with workers in a range of roles and from diverse settings across Ecuador, our analysis aims to better understand the genesis of pressure, how people respond to it and to gain insights into managing it more effectively, especially with a view to reducing workplace errors and staff burnout. Rather than imposing preformulated definitions of either 'pressure' or 'performance', we took an emic approach to gain a fresh understanding of how workers themselves experience, describe and make sense of workplace pressure. This article catalogues a wide range of pressures as experienced by our participants and maps relationships between them. We argue that while individuals are often held responsible for workplace errors, both 'pressure' and 'performance' are multifactorial, involving individuals, teams, case complexity, expertise and organizational systems and these must be considered in order to gain better understandings of performing under pressure.